AB0492 Mortality in Systemic Lupus Erythematosus: Causes and Risk Factors in A Group of Tunisian Patients. (15th July 2016) - Ben Salem, T.; Tougorti, M.; Naceur, I.; Lamloum, M.; Khanfir, M.; Ben Ghorbel, I.; Houman, M.H.
Abstract : Background: Mortality risk in patients with (SLE) is higher than in general population. The aim of this study was to determine mortality causes in a group of SLE patients. Methods: A retrospective study of patients who fulfilled the revised ACR criteria of SLE and admitted in an Internal Medicine department from 2000 to 2013. Data were recorded and analyzed for clinical, biological manifestations, infections and complications. Mortality causes were noted. Results: Twenty three patients out of 246 SLE patients died (9.3%). They were 22 female and 1 male. Mean age at disease onset 33.5±16.1 years. During SLE course, patients presented with arthralgia (n=21), pericardial effusion (n=15), lupus nephritis (n=14), pleural effusion (n=9), hepatitis (n=7), neurologic manifestations (n=6) and pulmonary hypertension (n=2). Patients were given corticosteroid in 95.6% of cases and immunosuppressive drugs in 60.8% of cases. Immunosuppressive treatment were based on cyclophosphamide (n=10), azathioprine (n=7), mycophenolate Mofetil (n=2) and cyclosporine (n=1). SLE was in remission in 82.6% of cases when death occurred and four patients were in relapse without other conditions. Death was related to infections in 13 cases: pneumonia (n=5), urinary tract infection (n=4), skin infection (n=2), tuberculosis (n=1) and pulmonary aspergillosis (n=1). Three patients had cancer (one lung cancer, one cecum cancer and one still indeterminate). Death occurred in two patients because of heart failure and was related to a severe pulmonary hypertension. Pericarditis (65.2% vs 36.9%; p=0.01), anti-histone antibodies (83.3% vs 49%; p=0.031) and infections (91.3% vs 60.1%; p=0.004) were statistically more frequent in dead patients. Lupus nephritis was also more frequent in these patients (63.6% vs 43%; p=0.068). Conclusions: Pericarditis and lupus nephritis were a poor factor prognosis in our series. Infection was the main cause of mortality in our patients. In addition to immunosuppression, poor socioeconomic status and lack of health care access in some patients can explain this high prevalence. Disclosure of Interest: None declared